Sedimentological and geochemical investigations of hydrothermally impacted sediments at the Aurora vent field, Fram Strait - Bjørnå, Eivind Urbye (UiT Norges arktiske universitet, 2023)
Hydrothermal vents are the result of the interaction between seawater and magma and occur at regular intervals along mid ocean ridges. The first visual confirmation of plumes was done in 1977. The detection of hydrothermal plumes has both provided indirect evidence for their existence and a resolution of the occurrences . In deep ocean with low sedimentation rates, hydrothermal plumites have the potential to become the dominant sediments. The Aurora seamount (roughly 82.9 north and 6,2 west) sits at the western end of Gakkel Ridge, 166 km from the nearest landmass, with estimated annual seafloor spreading is around 14 mm per year. The presence of venting in water above the seamount was proven in 2001, and visual confirmation of the vent field was done in 2014. The samples analyzed in this study was gathered on and around the Aurora seamount with multi, blade, and gravity cores during the HACON cruises in 2019 and 2021. Shallow samples were the focus of stable carbon and nitrogen analyses, grain size analysis, quantitative XRF and XRD in order to describe the biogeochemistry and mineralogy on the vent field. Gravity cores distal to the vent field were described visually and scanned by Multi Sensor Core Logger in order to provide a basis for correlation between different lithologic units. Findings in this study are the presence of rich deposits of iron and cupper sulfides in mounds on the rims of vents, responsible for providing sustenance to the chemolithoautotrophic communities. Only one sample from circa 1 m depth in a gravity core and 400 m south of the Aurora Vent Field was dated back to right before the Last Glacial Maxima (27123 to 27344 cal.yr. BP). However, it was not enough to accurately determine timing of different plumite layers. This study provides one estimate for annual average accumulation rates at the on the flanks of the Aurora seamount.